2017
DOI: 10.1186/s12885-016-3007-5
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C inhibitor Gö6976 but not Gö6983 induces the reversion of E- to N-cadherin switch and metastatic phenotype in melanoma: identification of the role of protein kinase D1

Abstract: BackgroundMelanoma is a highly metastatic type of cancer that is resistant to all standard anticancer therapies and thus has a poor prognosis. Therefore, metastatic melanoma represents a significant clinical problem and requires novel and effective targeted therapies. The protein kinase C (PKC) family comprises multiple isoforms of serine/threonine kinases that possess distinct roles in cancer development and progression. In this study, we determined whether inhibition of PKC could revert a major process requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 72 publications
(90 reference statements)
0
20
2
Order By: Relevance
“…Pharmacological inhibition or siRNA-mediated depletion of PKD1 has previously shown cytotoxicity in melanoma, breast cancer, prostate cancer and pancreatic cancer cells [ 11 , 13 , 19 , 25 , 27 ]. The CRT0066101 compound was also able to inhibit tumor growth of MCF7 chemoresistant xenografts in vivo [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological inhibition or siRNA-mediated depletion of PKD1 has previously shown cytotoxicity in melanoma, breast cancer, prostate cancer and pancreatic cancer cells [ 11 , 13 , 19 , 25 , 27 ]. The CRT0066101 compound was also able to inhibit tumor growth of MCF7 chemoresistant xenografts in vivo [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an atypical protein kinase C (PKC) activated by growth factors, mitogenic neuropeptides, as well as oxidative stress [ 9 ]. PKD1 regulates a variety of biological processes such as cell proliferation, survival, motility, organization of the Golgi apparatus and membrane trafficking [ 10 , 11 ]. Hotspot activating mutations of PRKD1 have recently been identified in polymorphous low-grade adenocarcinomas of salivary glands and likely constitute oncogenic drivers in these tumors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis does not however provide an explanation as to why the prodifferentiative PKD2 would be the most abundantly expressed in actively dividing cells. In hyperplastic human skin disorders, such as melanoma (40), basal cell carcinoma, and psoriasis (37), PKD1 was found to be upregulated. Taken together, these data suggest that, despite the fact that PKD1 seems not to be of primary importance in normal skin homeostasis (35), it has, whatever the species models, an evident proproliferative role in the context of skin carcinogenesis, wound healing, and other skin hyperproliferative diseases like psoriasis.…”
Section: Pkd1 As a Proproliferative And Prosurvival Factor In Skin Camentioning
confidence: 99%
“…Consequently, these data also suggest why targeting PKD1, by relatively selective inhibitors, has to be considered as an option for the treatment and prevention of epidermal tumorigenesis, and for other hyperproliferative diseases such as psoriasis. To this goal, we showed that inhibition of PKD1 in melanoma cells (i) decreased their colony-forming capacities probably through the regulation of the ERK, JNK, and NFkB signaling pathways, and (ii) induced the relocation of b-catenin from nucleus to plasma membrane, and the subsequent expression decrease of some proproliferative target genes such as cyclin D1 (40).…”
Section: Pkd1 As a Proproliferative And Prosurvival Factor In Skin Camentioning
confidence: 99%
“…Exogenous SCF was employed to induce phosphorylation of c-KIT (T703 site) and PKC-A (Thr638) [ 31 ]. Go-6976, an inhibitor of PKC [ 32 ], was employed to simulate PKC suppression. HCT116 cells were divided into seven groups: (1) DSMO as control, (2-3) (+)-UA (8 μ M, 24 or 48 hours), (4) SCF (100 ng/ml, 30 minutes), (5-6) (+)-UA (8 μ M, 24 or 48 hours) + SCF (100 ng/ml, 30 minutes), and (7) SCF (100 ng/ml, 30 min) + Go-6976 (6 μ M, 30 min).…”
Section: Methodsmentioning
confidence: 99%